The Ottomans and the Balkans : a discussion of historiography - Adanır, Fikret; Faroqhi, Suraiya, 1941- (Ottoman Empire and its heritage, 2002)
A discussion of historiography concerning the Ottoman Empire. It analyzes how the historiographies established in various national states have viewed the Empire and its legacy, and explores the links of 20th-century historiography with the rich historical tradition of the Ottoman Empire itself.